PEMBELAJARAN MATEMATIKA MODEL GENERATIVE LEARNING DENGAN PERFORMANCE ASSESSMENT UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS PADA SISWA KELAS VIII - Tutut Widiastuti Anisa; Masrukan Masrukan; Dwijanto Dwijanto (INSPIRAMATIKA, 2017)
This study aims to develop the mathematical learning materials with Generative Learning Model with Performance Assessment are introduction, focusing, challenge, and application for materials cube and cuboid, so that a learning becames valid, practical and the study is effective, so that a learning becames valid, practical and the study is effective and using a modified 4-D model. The development of learning outcomes as follows: (1) learning tools developed by the average value of validation of the syllabus 4,74, RPP 4,58, Student Book 4,81, LKS 4,73, and TKBK 4,36. (2) the practical learning with (a) the questionnaire responses of students reached 82%, and (b) the ability of the teacher in the learning management reached 89.25. (3) the process effectively, characterized by (a) the critical thinking abilities to achieve KKM is 70, and the proportion of students who earn a minimum value equal to 70 by 80% , (b) the average class TKBK test device better than the control class, and (c) the effect of attitudes and skills of the students' TKBK to reach 62.3%. It was concluded that the valid, practical use and effective learning